EFFECT OF FINANCIAL STABILITY, TARGET FINANCE, AND EXTERNAL PRESSURE AGAINST FINANCIAL STATEMENT FRAUD (STUDY ON IDX SHARIA GROWTH COMPANY LISTED ON THE INDONESIAN STOCK EXCHANGE) - Rusandry, Rusandry (Yayasan Nusantara Hasana Berdikari, 2025)
According to the Association of Certified Fraud Examiners (ACFE), financial statement fraud is a disclosure of a company's financial condition that is intentionally made false, which can be done by omitting certain values ​​in a financial report that is intended to deceive financial statement users. The aim of this research is to determine and analyze the influence of financial stability, financial targets and external pressure on fraudulent financial statements. The method in this research is a quantitative method. The data source in this research is secondary data in the form of annual reports on the BEI website. The data collection method uses purposive sampling. The population in this study are all IDX Sharia Growth companies listed on the Indonesia Stock Exchange for the 2022-2023 period. So a sample of 14 companies was obtained. Panel data analysis model with the help of Eviews 12 software. The research results show that financial stability has a positive effect on financial report fraud. Meanwhile, financial targets and external pressure have no effect on financial report fraud.